Production of Nutritional and Functional Jam from Cayenne Pepper - Titilade, Adeleke Elizabeth; Funmilayo, Abioye Victoria (Darul Yasin Al Sys, 2024)
Cayenne peppers are high in nutritional value, antioxidant properties but highly perishable like any other fresh fruits and vegetables. Fresh pepper is highly perishable and deteriorates within a few days after harvest without proper storage or preservation measures. The economic importance of Cayenne peppers is remarkable. In addition, their perishability is high and their added-value is low. Thus, it is important to find ways to improve their shelf life and add value to the crop. Therefore, there is need to study the processing of cayenne pepper into value added product such as Jam. Fresh cayenne peppers was sorted, washed, sliced into smaller sizes and homogenized. The homogenized pulp was heated, sweetners, pectin was added and jam was produced. The produced jam was subjected to physiochemical, texture and sensory evaluation. All data obtained was subjected to statistical analysis using Analysis of variance ANOVA. The results showed that the physiochemical composition of cayenne pepper ranged from 12.76 to 12.89 ˚Brix, 121.28 to 122.11 mg/100g; 2.85 to 2.49mg/100g; 0.31 to 0.39%; 47.35 to 49.17%; 97.67 to 111.67 for total soluble solid (TSS), vitamin C, carotenoid, total titrable acidity, DPPH and phenolic, respectively. The texture ranged from 0.27 to 3.93; 0.78 to 0.94; 1.56 to 9.11; 0.29 to 1.54; 0.38 to 0.89; 0.15 to 0.36; 0.42 to 1.11; 0.01 to 0.03; 15.18 to 15.25 for Hardness, springiness, adhesiveness, cohesiveness, chewiness, fracturability, gumminess, energy to peak and springiness, respectively. Yoruba pepper jam with date were well accepted among the samples in terms of all the attributes (colour, aroma, firmness, gelatinous, taste, mouthfeel and overall acceptability), followed by hausa pepper jam with date, yoruba pepper jam with sugar and hausa pepper jam with sugar. It could be deduced from the results that the present study that production of jam using different sweeteners (date and sugar) and from different varieties of cayenne pepper (Yoruba and Hausa) has great potentials. Yoruba cayenne pepper had better TSS, vitamin C, carotenoids, TTA and total phenol. All the sensory attributes indicated that the jam blends were well acceptable to the consumers especially the colour, aroma, firmness, gelatinous, taste, mouthfeel and overall acceptability but cayenne Hausa (sugar and date) had the best sensory attributes but yoruba pepper jam with date were well accepted among the samples in terms of all the attributes (colour, aroma, firmness, gelatinous, taste, mouthfeel and overall acceptability), followed by hausa pepper jam with date, yoruba pepper jam with sugar and hausa pepper jam with sugar. Processing of cayenne pepper into jam using different sweeteners will help in reducing post-harvest losses of the pepper and also enhance the utilization potential of the pepper.